Efficacy and Tolerance of Blended Diets in Children Receiving Gastrostomy Feeds. (24th September 2019) - Batsis, Irini D.; Davis, Laura; Prichett, Laura; Wu, Linxuan; Shores, Darla; Au Yeung, Karla; Oliva‐ Hemker, Maria
Abstract: Background: To determine the prevalence of gastrointestinal (GI) symptoms in children receiving a blended diet via a gastrostomy tube. Methods: This is a single‐center, retrospective study of children ages 1–18 years that received a blended diet. We reviewed demographics, anthropometrics, clinical characteristics, and rationale for switching to blended diet. Fixed‐effects logistic regression analysis was used to evaluate the changes in patient symptoms over the 12‐month follow‐up period, and fixed‐effects regression was employed to test for changes in anthropometrics. Results: Twenty‐three patients (8 female, 15 male) were identified, and data from 89 outpatient visits were analyzed. The most common underlying diagnosis was neurological disorder. Thirty‐five percent of patients received commercial whole cow milk formulas, 30% received hydrolysate formulas, and 35% received amino acid−based formulas. After formula switches were made, 65% received homemade blended diets, 17.5% received commercial blended diets, and 17.5% received a combination of both. Median duration of time on a blended diet was 17 months. Ninety‐five percent of patients who were previously experiencing upper GI symptoms improved within the first 3 months after blended diet initiation. Twenty‐one percent of patients developed mild constipation on the diet, which was managed with increased water intake and/or polyethylene glycol. Only 2 patients discontinued the blended diet, because of inadequate weight gain and worsening of upper GI symptoms. Conclusions: In our study population, blended diets were well tolerated in gastrostomy‐fed children and were associated with clinical improvement of upper GI symptoms.